Impact on CO2/N2 and CO2/CH4 separation performance using Cu-BTC with supported ionic liquids-based mixed matrix membranes - Monteiro, Bernardo (2018)
PTDC/CTM-POL/2676/2014 IF/00505/2014 This work was performed under the project "SunStorage-Harvesting and storage of solar energy", with reference POCI-01-0145-FEDER-016387, funded by European Regional Development Fund (ERDF), through COMPETE 2020-Operational Programme for Competitiveness and Internationalization (OPCI), and by national funds, through FCT-Fundacao para a Ciencia e a Tecnologia I.P. This work was supported by the Associated Laboratory for Sustainable Chemistry-Clean Processes and Technologies-LAQV which is financed by national funds from FCT/MEC (UID/QUI/50006/2013) and cofinanced by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007265) The NMR spectrometers are part of The National NMR Facility, supported by Fundacao para a Ciencia e a Tecnologia (RECI/BBB-BQB/0230/2012). A.R.N. and L.A.N. acknowledge FCT/MCTES for financial support through project PTDC/CTM-POL/2676/2014 and FCT Investigator Contract IF/00505/2014, respectively. C2TN/IST authors gratefully acknowledge the Fundacao para a Ciencia e Tecnologia support through the UID/Multi/04349/2013 project.